Analisis Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Pada PT Masuya Graha Trikencana Bekasi (Mulia Pratama, 2023)
The purpose of this study is to obtain a clearer picture of the effect of product quality and price on the decision to purchase frozen food and instant noodles at PT Masuya Graha Trikencana Bekasi. The method used in this research is classical assumption test analysis, multiple linear regression analysis and goodness of fit test, using SPSS 26. To increase the level of purchase of PT Masuya Graha Trikencana Bekasi, one of the things that is done is to sell frozen food and instant noodle products which are quality and provide consistent prices. With quality products and consistent prices, it is expected to increase PT Masuya Graha Trikencana Bekasi's purchases. In analyzing the relationship between the effect of product quality and price on purchasing decisions, by knowing the strength and weakness of the relationship between the independent factor X (product quality and price) and the dependent factor Y (purchasing level), then multiple linear regression analysis is used. Based on the calculation of multiple linear regression analysis, the results obtained are Y = 1.209 + 0.489 X1 + 0.520 X2. From the results of calculating the coefficient of multiple linear regression analysis, it can be seen that it has a positive relationship, meaning that product quality and prices applied by PT Masuya Graha Trikencana Bekasi can increase purchasing decisions. From the results of the calculation of the coefficient of determination analysis shows that product quality and price have an influence on purchasing decisions of 46.3% and the remaining 53.7% is influenced by other factors. The results of the t-test hypothesis test both product quality and price have the same value: tcount > ttable, namely the product quality value is 3.461 > 2.030 and the price value is 3.000 > 2.030. It can be concluded that there is a significant influence of product quality and price variables on purchasing decisions. Based on the results of the F (simultaneous) test calculations, it was found that the Fcount value was greater than Ftable (13.813 > 3.27), so it was concluded that there was a significant influence between product quality and price on purchasing decisions.